Changing Epidemiology of Oral Cavity Cancer in the United States. (5th February 2023) - Stepan, Katelyn O.; Mazul, Angela L.; Larson, Jeffrey; Shah, Parth; Jackson, Ryan S.; Pipkorn, Patrik; Kang, Stephen Y.; Puram, Sidharth V.
Abstract: Objective: We aim to more accurately characterize the current distribution and rates of squamous cell carcinoma (SCC) cases across various oral cavity subsites in the United States. Study Design: Retrospective cohort. Setting: Database study evaluating cancer incidence in the United States from 2001 to 2017. Methods: We utilized the US Cancer Statistics Public Use Database, which includes deidentified cancer data reported to the Centers for Disease Control and Prevention's National Program of Cancer Registries and the National Cancer Institute's SEER (Surveillance, Epidemiology, and End Results), capturing 97% of newly diagnosed cancers. We restricted our analysis to SCC arising from oral cavity subsites from 2001 to 2017. We calculated trends in annual cancer incidence rates using SEER*Stat, as well as annual and average annual percentage change and joinpoints with the National Cancer Institute's Joinpoint program. Results: Most oral cavity SCC cases arise from the oral tongue (41.7%), followed equally by lip and floor of mouth (each 16.5%), gingival (10.6%), buccal (6.7%), retromolar trigone (5.6%), and hard palate (2.3%) involvement. The overall incidence of oral tongue SCC continues to rise with an average annual percentage change of 1.8% (95% CI, 1.6%‐2.1%; P < .001), with a 2.3% increase among women. This increase is seen among males and females of all age groups. Cancers involving the gum, buccal mucosa, and hard palate were also found to be increasing in rate, albeit to a lesser degree and with substantially lower incidence. Conclusions: The tongue is the most frequently involved subsite of oral cavity SCC and is increasing in incidence among males and females of all ages.